2014
DOI: 10.1002/anie.201310164
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of the Antimitotic Marine Macrolide (−)‐Leiodermatolide

Abstract: Leiodermatolide is an antimitotic macrolide isolated from the marine sponge Leiodermatium sp. whose potentially novel tubulin-targeting mechanism of action makes it an exciting lead for anticancer drug discovery. In pursuit of a sustainable supply, we report a highly stereocontrolled total synthesis (3.2 % yield) based on a convergent sequence of palladium-mediated fragment assembly and macrolactonization. Boron-mediated aldol reactions were used to configure the three key fragments 2, 5, and 6 by employing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 53 publications
2
19
0
Order By: Relevance
“…Our successful total synthesis of (−)‐leiodermatolide provided further verification of the assigned 3D structure 5 . While our initial studies towards the construction of the leiodermatolide macrocycle and side chain provided strong support for the relative configuration proposed in 5 , this plan proved to be unsuitable for achieving the total synthesis itself.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Our successful total synthesis of (−)‐leiodermatolide provided further verification of the assigned 3D structure 5 . While our initial studies towards the construction of the leiodermatolide macrocycle and side chain provided strong support for the relative configuration proposed in 5 , this plan proved to be unsuitable for achieving the total synthesis itself.…”
Section: Discussionsupporting
confidence: 55%
“…Completion of the synthesis of 5 from this point, however, required modification of our initial strategy. The remainder of this review details these efforts, leading to our successful total synthesis of (−)‐leiodermatolide …”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, they found that both diastereoisomers were almost indistinguishable from their 13 C NMR data, and only subtle differences in the 1 H NMR spectra could be observed to indisputably assign 31 as the correct leiodermatolide . In the meantime, the Paterson group reported their highly stereocontrolled total synthesis of leioermatolide employing a convergent palladium‐mediated fragment assembly and macrolactonization sequence, providing further experimental confirmation of the natural product structure …”
Section: Dp4mentioning
confidence: 99%
“…However, such discrepancies were enough to indisputably determine that the correct relative and absolute configuration of leiodermatolide was 75 (the same that Paterson et al 51 arbitrarily drawn in the original publication). The structure of leiodermatolide was further validated and re-confirmed by Paterson et al, 55 using a stereocontrolled total synthesis approach based on a convergent palladium-mediated assembly and macrolactonization sequence.…”
Section: Leiodermatolidementioning
confidence: 96%